Firm-Level Investment Decisions Under Uncertainty and Irreversibility in Zimbabwes Private Firms - Muzurura, Joe (International Journal of Business, Economics and Management, 2018)
Zimbabwe’s business operating environment is abounding with both micro and macro uncertainties that regularly impact on firm-level investment decisions. Under uncertainty and irreversibility private firms are forced to integrate into their investment appraisals and decisions some expectations regarding future product demand and prices, likely returns on fixed capital investment, expected margins, cost of capital expectations and cash flow projections. These important issues are not known with definitive assurance and hence, making investment decisions under uncertainty a challenging task for Zimbabwe’s private firms. The study examined investment under uncertainty and irreversibility in Zimbabwe’s private firms using a polychotomous regression model with the three investment decision outcomes; “invest now”, “do not invest now” and “defer investment”. The major findings are that; (1) liquidity constraints, firm size and credit constraints significantly influence the probability of investing now irrespective of uncertainties in the economy. (2) Poor public infrastructure, political uncertainty, inconsistent application of the indigenization laws and absence of laws that protect private property rights increase the probability of private firms’ deferring investment decisions under uncertainty and investment irreversibility. The paper recommends that policy makers should reduce macro uncertainties in the financial sector that affect firm-level investment decisions, adopt policies that enhance productivity of public infrastructure and must observe national and international laws that safeguard investor property rights.